Application of 3D -Technologies in the Field of Preservation and Use of Archaeological Heritage - Denisov Igor V.; Zubov Sergey E.; Bukina Olga V. (Археология евразийских степей, 2022)
The article covers the issues of choosing and specific using the various methods of digitizing archaeological sites and artifacts to generate 3D models. The authors identify three main objectives of creating 3D-models of archaeological sites and artifacts: 1) research work; 2) storage of a copy in case of possible damage (loss) of the original and 3) remote visual display for the popularization of the archaeological heritage. Photogrammetry and laser scanning are considered to be the main methods of digitizing archaeological sites and artifacts. The organizational and methodological features of using photogrammetry method to generate 3D-models of archaeological artifacts and sites are considered separately: the selection of equipment, arrangement of workspace for photogrammetry of artifacts in steady-state conditions and the procedure for its implementation, as well as the recommendations for conducting photogrammetry of archaeological objects in the field.